Prevalence, antimicrobial resistance pattern, and associated factors of Salmonella and Shigella among under five diarrheic children attending public health facilities in Debre Markos town, Northwest Ethiopia - Dessale, Mesfin; Mengistu, Getachew; Mengist, Hylemariam Mihiretie (Frontiers in Public Health, 2023)
Background Under five children are at risk of diarrhea-associated morbidity and mortality. Salmonella and Shigella are major causes of diarrhea in under-five children, especially in developing countries. This study aimed to assess the prevalence, antimicrobial resistance pattern, and associated factors of Salmonella and Shigella among under-five diarrheic children in Debre Markos town public health facilities. Methods A cross-sectional study was conducted at public health facilities in Debre Markos town using a consecutive convenient sampling technique. Data on socio-demographic and associated factors were collected using a structured questionnaire. Salmonella serovars and Shigella species were identified using MacConkey, Xylose Lysine Deoxycholate, Salmonella Shigella agar, and biochemical tests. The antimicrobial resistance pattern was determined by using the modified Kirby-Bauer disk diffusion technique. Results The overall prevalence of Salmonella and Shigella was 11.7% (26/222; 95% CI = 7.2–17.5%). Isolated Salmonella serovars showed a higher rate of resistance (85.7%, 6/7) for both Ampicillin and Amoxicillin/Clavulanic acid while Shigella isolates showed a higher resistance rate to Amoxicillin/Clavulanic acid (78.9%, 15/19) and Ampicillin (73.7%, 14/19). The overall multidrug resistance (MDR) rate of Salmonella and Shigella isolates was 88.5% (23/26). Parent/guardian educational status ≤ elementary school (AOR = 3.783; 95% CI = 1.28–11.19; P = 0.016), presence of two or more under-five children in the family (AOR = 8.999; 95% CI = 2.93–27.69; P < 0.001), unimproved source of drinking water (AOR = 5.010; 95% CI = 1.56–16.10; P = 0.007), the habit of storing cooked foods for later use (AOR = 3.199; 95% CI = 1.07–9.54; P = 0.037), attendance of the child at social gatherings (AOR = 5.387; 95% CI = 1.78–16.35; P = 0.003), and infrequent child fingernail trimming (every ≥ 2 weeks; AOR = 4.693; 95% CI = 1.47–14.94; P = 0.009) showed statistically significant association with the prevalence of culture-confirmed Salmonella and Shigella isolates. Conclusion The prevalence of culture-confirmed Salmonella and Shigella isolates was significantly high in the study area. Salmonella and Shigella isolates exhibited a high rate of MDR pattern. Parent/guardian education level below the elementary school, the presence of two or more under-five children in the family, using unimproved water source, a habit of storing cooked food, and infrequent fingernail trimming were independent predictors of culture-confirmed Salmonella and Shigella. Therefore, besides public health measures, regular surveillance of the prevalence and antimicrobial resistance pattern of Salmonella and Shigella should be routinely practiced in the study setting.